Role of miRNAs in sucrose stress response, reactive oxygen species, and anthocyanin biosynthesis in Arabidopsis thaliana - Azad, Md. Fakhrul; Dawar, Pranav; Esim, Nevzat; Rock, Christopher D. (Frontiers in Plant Science, 2023)
In plants, sucrose is the main transported disaccharide that is the primary product of photosynthesis and controls a multitude of aspects of the plant life cycle including structure, growth, development, and stress response. Sucrose is a signaling molecule facilitating various stress adaptations by crosstalk with other hormones, but the molecular mechanisms are not well understood. Accumulation of high sucrose concentrations is a hallmark of many abiotic and biotic stresses resulting in the accumulation of reactive oxygen species and secondary metabolite anthocyanins that have antioxidant properties. Previous studies have shown that several MYeloBlastosis family/MYB transcription factors are positive and negative regulators of sucrose-induced anthocyanin accumulation and subject to microRNA (miRNA)-mediated post-transcriptional silencing, consistent with the notion that miRNAs may be ‘nodes’ in crosstalk signaling by virtue of their sequence-guided targeting of different homologous family members. In this study, we endeavored to uncover by deep sequencing small RNA and mRNA transcriptomes the effects of exogenous high sucrose stress on miRNA abundances and their validated target transcripts in Arabidopsis. We focused on genotype-by-treatment effects of high sucrose stress in Production of Anthocyanin Pigment 1-Dominant/pap1-D, an activation-tagged dominant allele of MYB75 transcription factor, a positive effector of secondary metabolite anthocyanin pathway. In the process we discovered links to reactive oxygen species signaling through miR158/161/173-targeted Pentatrico Peptide Repeat genes and two novel non-canonical targets of high sucrose-induced miR408 and miR398b*(star), relevant to carbon metabolic fluxes: Flavonoid 3'-Hydroxlase (F3'H), an important enzyme in determining the B-ring hydroxylation pattern of flavonoids, and ORANGE a post-translational regulator of Phytoene Synthase expression, respectively. Taken together, our results contribute to understanding the molecular mechanisms of carbon flux shifts from primary to secondary metabolites in response to high sugar stress.